The Role of Dividend Policy as a Mediator of the Relationship between Corporate Governance and Profitability on Firm Value - Lestiana, Eli; Purwidianti, Wida; Tubastuvi, Naelati; Widhiandono, Hengky (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
This analysis examines the role of dividend policy as a mediator in the relationship between corporate governance and profitability on firm value. The population studied consisted of 47 public banking companies listed on the Indonesia Stock Exchange during 2019-2023, with 87 research samples obtained through the purposive sampling method. The analysis confirmed that profitability significantly positively affects dividend policy and corporate governance positively influences firm value. However, corporate governance and dividend policy do not affect firm value, and dividend policy does not mediate the relationship between corporate governance and firm value, as well as between profitability and firm value. These findings confirm the importance of profitability and corporate governance in enhancing firm value through effective dividend policy.